More than gangsters and girl scouts: Environmental health perspectives of urban youth. (November 2018) - Bogar, Sandra; Young, Staci; Woodruff, Shane; Beyer, Kirsten; Mitchell, Rod; Johnson, Sheri
Abstract: The purpose of this study was to explore environmental health perspectives among urban youth. A total of 12 focus groups with 64 youth were conducted. Youth defined environmental health in a multidimensional manner which integrated aspects of the physical, social, and built environment and concentrated on the neighborhood context. A theme of environmental health resilience factors and sub-themes of safety, trust, engagement, leadership, and representation were identified and described. A second theme of underlying structural drivers of environmental health with sub-themes of equitable opportunities and power inform environmental health. A conceptual model was developed to guide future environmental health research and action. Highlights: Urban youths' environmental health definitions and conceptualizations are described. Environmental health resilience factors and underlying structural drivers are identified. A conceptual model informs future action and evaluation.